Penerapan Enterprise Architecture Pada Perusahaan Manufaktur Baja di Era Industri 4.0 - Boy Muhammad Ridwan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Currently, it is time for companies in the manufacturing sector to implement information technology planning by following the developments of the 4.0 industrial era. Competition in this era requires companies to be efficient in all things, so they can win the increasingly fierce competition. One of them is by revamping the existing system in the company so that it can transform into a steel manufacturing company that is fully supported by a technology information system. The use of TOGAF as a framework in fulfilling the Business Architecture is very appropriate. Currently, the TOGAF Framework is one of the most widely used methods, considering that it is very simple to use. The discussion in this method is Business Architecture, Application Architecture, Information Architecture and Technology Architecture. The purpose of implementing Enterprose Architecture in manufacturing companies is to obtain information technology plans that can make efficiency and support company operations, so that they are more efficient and effective and can win the competition in the industrial era 4.0.